Why Study Schizophyllum? - Carlene A. Raper; Thomas J. Fowler (Fungal Genetics Reports, 2004)
For its fascinating sex life, of course! The German mycologist Hans Kniep (1930) was the first to discover that the wood-rotting basidiomycete, Schizophyllum commune, recombines its genome regularly and propagates effectively by consorting with any one of many compatible mates through a system known as tetrapolar sexuality, a term describing the meiotic segregation of four different mating types.